Culture of leukocyte-derived cells from human peripheral blood: Increased expression of pluripotent genes OCT4, NANOG, SOX2, self-renewal gene TERT and plasticity. Issue 3 (20th January 2023) - Lee, Yi-Jen; Wang, Jehng-Kang; Pai, Yu-Ming; Frost, Alan; Viprakasit, Vip; Ekwattanakit, Supachai; Chin, Hui-Chieh; Liu, Jah-Yao
Abstract : There are few stem cells in human peripheral blood (PB). Increasing the population and plasticity of stem cells in PB and applying it to regenerative medicine require suitable culture methods. In this study, leukocyte populations 250 mL of PB were collected using a blood separator before that were cultured in optimal cell culture medium for 4 to 7 days. After culturing, stemness characteristics were analyzed, and red blood cells were removed from the cultured cells. In our results, stemness markers of the leukocyte populations Sca-1 + CD45 +, CD117 + CD45 +, and very small embryonic-like stem cells CD34 + Lin − CD45 − and CXCR4 + Lin − CD45 − were significantly increased. Furthermore, the expression of stem cell genes OCT4 (POU5F1 ), NANOG, SOX2, and the self-renewal gene TERT was analyzed by quantitative real-time polymerase chain reaction in these cells, and it showed a significant increase. These cells could be candidates for multi-potential cells and were further induced using trans-differentiation culture methods. These cells showed multiple differentiation potentials for osteocytes, nerve cells, cardiomyocytes, and hepatocytes. These results indicate that appropriate culture methods can be applied to increase expression of pluripotent genes and plasticity. Leukocytes of human PB can be induced to trans-differentiate into pluripotent potential cells, which will be an important breakthrough in regenerative medicine.